Civilized Values of Commands and Prohibitions in the Hajj Verses from Surat Al-Baqarah, Al-Imran, Al-Ma’idah and Hajj (Islamic Sciences Journal, 2023)
ABSTRACT                          Hajj is a great worship that Muslims witness every year, but many of them neglect the civilizational features for which this great conference is being held in the Sacred House of Allah, and the lack of contemplation of the great purposes for which the Hajj was legislated, and they are preoccupied with accurate legal rulings with their importance and the Muslim’s need for them. Without thinking in the goals, governance and connotations whose knowledge strengthens the reform of souls and advancement in the ladder of values ​​for the leadership and advancement of societies. Through careful reading of Surat Al-Hajj and Surat Al-Baqarah and Al-Imran, I found the noble verses full of clear signs and indications of the supremacy of Islam and its noble goals in establishing firm rules that require the Muslim to work and contribute in building and completing the lofty edifice of the civilization of Islam. I was very keen in researching the inspiration of the spirit of the Qur’anic text and its implications by referring to the original refrences of interpretation and seeking the assistance of what they brought of interpretation and explanation, with reference to the books of contemporaries and their deductions, and this is what I have strived to highlight in this research.
Keywords: Provision, meanings of brotherhood, command, non-shirk, purification of souls, prohibition .